Donor Atom Preference of Organoruthenium and Organorhodium Cations on the Interaction with Novel Ambidentate (N,N) and (O,O) Chelating Ligands in Aqueous Solution - Sándor Nagy; András Ozsváth; Attila Cs. Bényei; Etelka Farkas; Péter Buglyó (Molecules, 2021)
Two novel, pyridinone-based chelating ligands containing separated (O,O) and (Namino,Nhet) chelating sets (Namino = secondary amine; Nhet = pyrrole N for H(L3) (1-(3-(((1H-pyrrole-2-yl)methyl)-amino)propyl)-3-hydroxy-2-methylpyridin-4(1H)-one) or pyridine N for H(L5) (3-hydroxy-2-methyl-1-(3-((pyridin-2-ylmethyl)amino)propyl)pyridin-4(1H)-one)) were synthesized via reduction of the appropriate imines. Their proton dissociation processes were explored, and the molecular structures of two synthons were assessed by X-ray crystallography. These ambidentate chelating ligands are intended to develop Co(III)/PGM (PGM = platinum group metal) heterobimetallic multitargeted complexes with anticancer potential. To explore their metal ion binding ability, the interaction with Pd(II), [(η6-p-cym)Ru]2+ and [(η5-Cp*)Rh]2+ (p-cym = 1-methyl-4-isopropylbenzene, Cp* = pentamethyl-cyclopentadienyl anion) cations was studied in aqueous solution with the combined use of pH-potentiometry, NMR and HR ESI-MS. In general, organorhodium was found to form more labile complexes over ruthenium, while complexation of the (N,N) chelating set was slower than the processes of the pyridinone unit with (O,O) coordination. Formation of the organoruthenium complexes starts at lower pH (higher thermodynamic stabilities of the corresponding complexes) than for [(η5-Cp*)Rh]2+ but, due to the higher affinity of [η6-p-cym)Ru]2+ towards hydrolysis, the complexed ligands are capable of competing with hydroxide ion in a lesser extent than for the rhodium systems. As a result, under biologically relevant conditions, the rhodium binding effectivity of the ligands becomes comparable or even slightly higher than their effectivity towards ruthenium. Our results indicate that H(L3) is a less efficient (N,N) chelator for these metal ions than H(L5). Similarly, due to the relative effectivity of the (O,O) and (N,N) chelates at a 1:1 metal-ion-to-ligand ratio, H(L5) coordinates in a (N,N) manner to both cations in the whole pH range studied while, for H(L3), the complexation starts with (O,O) coordination. At a 2:1 metal-ion-to-ligand ratio, H(L3) cannot hinder the intensive hydrolysis of the second metal ion, although a small amount of 2:1 complex with [(η5-Cp*)Rh]2+ can also be detected.